Mechatronic smart training kit / Vishnukaanthan Raman, Prabeen Nair Jayavalan and Aiman Haqimi Roslee - Raman, Vishnukaanthan; Jayavalan, Prabeen Nair; Roslee, Aiman Haqimi (Universiti Teknologi MARA, Kedah, 2019)
Mechatronic Smart Training Kit is a teaching aids product for mechatronic basic subjects. It facilitates students and teachers in both practical and theoretical work. Understanding students in the Mechatronic field can be translated more concisely and compactly when students are able to complete the whole of the practical tasks contained in this Mechatronic Smart Training Kits. The objective of this Mechatronic Smart Training Kit is to solve problem during the lecture. This training can reduce the preparation time of the trainer for instructors. Instructors do not need to provide many tools to teach mechatronic subjects. In addition, this training kit helps to provide basic exposure about mechatronics to students. Students can understand the mechatronic concept by conducting this training kit. Not only that, students can handle this training kit easily without maximum supervision from the instructor. Compared to the existing training kits, Mechatronic Smart Training Kit is easy to maintain as the equipment used is easy to find in the market. Maintenance costs can also be reduce. This Mechatronic Smart Training Kit is built in with Electric, Electronic, Pneumatic and Program Logic Control (PLC) system . This training kit was generated by the materials and equipment available at the mechatronic workshop Training Industrial Institute Pedas. Thus, it does not involve much cost to build. The training kits also take less space than the trainers in the workshop. All the systems in this training can be carried out simultaneously or separately. Mechatronic Smart Training Kit is easy to create . Its also very useful product especially in learning mechatronic field. Since equipment and material are easily available in the market, the cost the making is much more lower than you purchase a new trainer . This Training kit has high potential in the market as leaning aid tool . Mechatronic Smart Training kit is the best platform for students to practice and learn basic mechatronic system. Further more this training it can be easily carry to other institute for training purpose